2023
DOI: 10.1021/acs.jpcc.2c08262
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Atom Doping Carbon Materials as Highly Efficient Electrocatalysts for Lithium–Sulfur Batteries: Bimetallic Cooperation Mechanism

Abstract: Due to the low sulfur utilization, slow battery kinetics, and shuttle effect of lithium polysulfides (LiPSs), the practical application of lithium−sulfur (Li−S) batteries is severely limited. Understanding the reaction mechanism is very important for the design and application of high-performance batteries. Herein, the adsorption mechanism of LiPSs, the reaction mechanism of a battery electrode, and the catalytic decomposition of LiPSs on pristine, single-atom, and dual-atom doping C 9 N 4 (C 9 N 4 , M/C 9 N 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Yao et al successfully synthesized Li 2 ZrCl 6 with an even higher Li + conductivity of 1 × 10 –3 S cm –1 , but the preparation process is comparatively intricate. In this case, ball-milling cups were opened every 12 h, followed by manual homogenization, and the total time for ball-milling was 84 h. On the other hand, previous studies have shown that the ionic conductivity can also be improved by doping with metal ions. Jung et al replaced partial Zr 4+ with In 3+ and Sc 3+ to increase the ionic conductivity of the annealed monoclinic-phase Li 2 ZrCl 6 from 7.1 × 10 –6 to 2.1 × 10 –3 S cm –1 . , Meanwhile, they found that Cr 3+ and V 3+ doping also can effectively enhance the ionic conductivity of Li 2 ZrCl 6 . However, ion doping may not only increase the cost of raw materials (like In 3+ and Sc 3+ ) or influence the environment (like Cr 3+ and V 3+ ) but also reduce the electrochemical stability of the electrolyte .…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al successfully synthesized Li 2 ZrCl 6 with an even higher Li + conductivity of 1 × 10 –3 S cm –1 , but the preparation process is comparatively intricate. In this case, ball-milling cups were opened every 12 h, followed by manual homogenization, and the total time for ball-milling was 84 h. On the other hand, previous studies have shown that the ionic conductivity can also be improved by doping with metal ions. Jung et al replaced partial Zr 4+ with In 3+ and Sc 3+ to increase the ionic conductivity of the annealed monoclinic-phase Li 2 ZrCl 6 from 7.1 × 10 –6 to 2.1 × 10 –3 S cm –1 . , Meanwhile, they found that Cr 3+ and V 3+ doping also can effectively enhance the ionic conductivity of Li 2 ZrCl 6 . However, ion doping may not only increase the cost of raw materials (like In 3+ and Sc 3+ ) or influence the environment (like Cr 3+ and V 3+ ) but also reduce the electrochemical stability of the electrolyte .…”
Section: Introductionmentioning
confidence: 99%
“…As of now, MO can be prepared by the heat treatment of MOFs in air . Although this one-step heat treatment is a facile and efficient strategy, the MO NPs always possess large average sizes and suffer from the pores missing, which leads to poor activity in heterogeneous catalysis. , To tackle this issue, general strategies consist of using supports with high surface area (e.g., SiO 2 and graphene) to stabilize and prevent NPs aggregation. , It was developed extensively for mesoporous materials because the structure of the materials can be replicated and the properties are manipulated . Tremendous efforts have been focused on improving the dispersity of active sites by this method .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, porous carbon materials have excellent electrical conductivity and can be used as a new type of photocatalyst for catalyzing CO 2 cycloaddition. However, pure carbon materials always lack active sites and often require cocatalysts to achieve high catalytic activity . Jiang and his colleagues developed a hollow porous carbon catalyst codoped with Zn and N by pyrolysis of the polystyrene spherical template ZIF-8, which is the first example reporting the photothermal effect of carbon-based materials decorated with single-atom catalysts for CO 2 fixation .…”
Section: Introductionmentioning
confidence: 99%